Analysis on women`s double tennis entries strength of 08 Olympic Games in china - Guo, K.; Chen, W.; Xing, X. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume III: Statistics and Managment in Sports., 2008)
Use of mathematical statistics, video analysis, comparative law, an objective analysis the technical and tactical use of effects after Chinese women's doubles tennis players participate in the match of " the Tennis Grand Slam Cup " between 2006 and 2007 .And with the outstanding athletes abroad for comparative studies. Main findings: (1) In 2006, Chinese women' doubles tennis players made better achivements, Zheng Jie / Yan Zi, and other combinations becoming more mature, with the impact of 08 Olympic medals strength, but at the same time results in the technical and tactical use with 08 Olympic competition the main opponents are still some differences. (2) Chinese women' doubles tennis setbacks year in 2007, such as Zheng Jie's injury problems and the new allocation of the doubles combinations not mature, a series of competitions in unsatisfactory results. And the Outlook is not optimistic. (3) To Russia, the United States, Spain, France, Belgium, and the other world outstanding female tennis athletes in 08 Olympic Games in China will pose a great women' doubles tennis resistance, they behalf of their respective countries to participate in both women's doubles competition impact of medals strength in 08 Olympic Games.